2020
DOI: 10.1155/2020/4590509
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gross Motor Function on the Oral Health-Related Quality of Life in Young Adults with Cerebral Palsy in Saudi Arabia

Abstract: Background. There is evidence that gross motor function impacts the health-related quality of life of young adults with cerebral palsy. This study aimed to assess gross motor function, oral health and oral health-related quality of life (OHRQoL), and the relationship between them in young adults with cerebral palsy. Methods. The sample comprised 46 individuals aged between 13 and 17 years with Gross Motor Function Classification Scores (GMFCS) ranging from level I to level III. The individuals and their parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…It is reported that children with cerebral palsy have a poor oral health related quality of life compared to children without cerebral palsy 48,49,68,69 . Motor function of children with cerebral palsy is reported to play a significant role for both oral health related quality of life and overall oral health in adolescents and young adults 70 . Dental caries and bruxism have been shown to have a negative impact on oral health related quality of life among children and adolescents with cerebral palsy 10,29 and negative impacts in regard to conditions such as the severity of dental caries, level of communication and family income 71 .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that children with cerebral palsy have a poor oral health related quality of life compared to children without cerebral palsy 48,49,68,69 . Motor function of children with cerebral palsy is reported to play a significant role for both oral health related quality of life and overall oral health in adolescents and young adults 70 . Dental caries and bruxism have been shown to have a negative impact on oral health related quality of life among children and adolescents with cerebral palsy 10,29 and negative impacts in regard to conditions such as the severity of dental caries, level of communication and family income 71 .…”
Section: Resultsmentioning
confidence: 99%
“…It is recognized that children with CP have a high rate of dental treatment needs ( 3 , 4 ). Considering the exponential demand for dental care in this population ( 14 ), it is necessary to understand the level of stress experienced during clinical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered the most common cause of physical disability in childhood ( 2 ). Children with CP require special medical and dental care because caries, periodontal diseases and malocclusions are relatively frequent ( 3 - 5 ), caused by difficulties in oral hygiene, dietary consistency, drugs, misinformation and limited access to dental services ( 6 ). Dental procedures usually are laborious due to the involuntary movements, constant spasms, marked stiffness and communication difficulties ( 2 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos Santos et al reported a higher prevalence of tooth decay in children with CP than in other diseases [9]. In another study, oral health-related quality of life decreased with increasing gross motor function, which seems to highlight the role of gross motor function in oral health in children with CP [10].…”
Section: Introductionmentioning
confidence: 85%